2007
DOI: 10.1103/physrevlett.99.015301
|View full text |Cite
|
Sign up to set email alerts
|

Oscillation Frequency Dependence of Nonclassical Rotation Inertia of SolidHe4

Abstract: The nonclassical rotational inertia fraction of the identical cylindrical solid 4He below 300 mK is studied at 496 and 1173 Hz by a double resonance torsional oscillator. Below 35 mK, the fractions are the same at sufficiently low rim velocities. Above 35 mK, the fraction is greater for the higher than the lower mode. The dissipation peak of the lower mode occurs at a temperature approximately 4 mK lower than that of the higher mode. The drive dependence of the two modes shows that the reduction of the fractio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

58
361
3
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(424 citation statements)
references
References 15 publications
58
361
3
2
Order By: Relevance
“…It is clear that the data and the expected temperature dependence do not match. If the much smaller superfluid density measured in our own [44] torsional oscillator with a cylindrical cell is assumed, then the expected temperature dependence (see solid line) is well within the scatter and the data is not inconsistent with the expectation. Since the cylindrical geometry of our torsional oscillator is closer to the present heat pulse experiment chamber, it is likely that this superfluid density is more appropriate.…”
Section: Velocity Of Heat Pulse Propagationsupporting
confidence: 53%
See 2 more Smart Citations
“…It is clear that the data and the expected temperature dependence do not match. If the much smaller superfluid density measured in our own [44] torsional oscillator with a cylindrical cell is assumed, then the expected temperature dependence (see solid line) is well within the scatter and the data is not inconsistent with the expectation. Since the cylindrical geometry of our torsional oscillator is closer to the present heat pulse experiment chamber, it is likely that this superfluid density is more appropriate.…”
Section: Velocity Of Heat Pulse Propagationsupporting
confidence: 53%
“…The relation, if any, between the reduction in superfluid density as seen in critical velocity effects in the torsional oscillator experiments [5,44] and the excitation energy in our heat pulse generator is important to investigate. Kim and Chan [38] found that the measured superfluid fraction was dependent on the amplitudes of the solid 4 He velocity: the fraction was nearly constant up to about 10 mm/s and it decreased at amplitudes higher than this.…”
Section: Velocity Of Heat Pulse Propagationmentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing the concentration of 3 He impurities, 3 , x from below 0.1 ppb to 10 ppm, * T systematically increases from ~ 20 to ~ 200 mK [12]. Increasing frequency of oscillations by a small amount resulted in an increase in * T [13]. The effect was the largest in the most disordered samples, but can be reduced upon annealing and was absent in perfect monocrystals.…”
Section: Solid Heliummentioning
confidence: 95%
“…This, termed the nonclassical rotational inertia (NCRI), is the strongest evidence yet for the existence of a supersolid. While these experiments have been much reproduced [6][7][8][9], another line of experiment has been to focus on particular aspects of the helium sample, such as the annealing process or the measurement of the shear modulus, which might suggest another explanation for the apparent existence of the supersolid phase. The annealing process has been shown to dramatically reduce the superfluid fraction [10,11], while the shear modulus displays a similar dependence to the NCRI [12].…”
mentioning
confidence: 99%